Children and Armed Conflict
XIV, 250 p.
Keywords: Exploring the experiences of children encountering war and armed conflict, this book draws upon history, ethnography, sociology, literature, media studies, psychology, public policy, and other disciplines to address children as soldiers, refugees, and peace-builders within their social, cultural, and political contexts.